A rapid review of advanced life support guidelines for cardiac arrest associated with anaphylaxis. (February 2021) - McLure, Michael; Eastwood, Kathryn; Parr, Michael; Bray, Janet
Abstract: Background: We conducted a rapid review of current international and Australian advanced life support (ALS) guidelines for cardiac arrest associated with anaphylaxis to (1) assess the variation and (2) determine if a systematic review update of ALS guideline recommendations is warranted. Method: A search and comparison of key recommendations was conducted for major international and Australian clinical guidelines, including member societies and councils of the World Allergy Organisation and the International Liaison Committee on Resuscitation (ILCOR). Systematic database searches (Medline, Cochrane Database of Systematic Reviews, PROSPERO international register of systematic reviews and ClinicalTrials.gov databases) was conducted to identify existing and in-progress research published on the topic of anaphylaxis and cardiac arrest. Results: Eight international guidelines were identified from Australia/New Zealand, Europe, United States and Canada, and 5 national guidelines were identified for Australia. There was general consensus across all guidelines for the use of adrenaline, oxygen, patient positioning and glucagon. There was variation across international and Australian guidelines for adrenaline dosing and frequency, antihistamines and corticosteroid recommendations. Most recommendations were based on low-level evidence, and the review of published systematic reviews and clinical trials identified new evidence in the last decade. Conclusions: We found significant variation between current ALS guideline recommendations for treating anaphylaxis. While there is no new evidence to suggest a systematic review of guideline recommendations is needed, there may be an opportunity to produce more consistent international guideline recommendations and educational materials.